Protection of Non-Traditional Trademarks under Sri Lankan Law: A Critical Perspective - Kamardeen, N. (Faculty of Law, University of Colombo, 2022)
In the past few years, there has been some debate as to whether non-traditional trademarks (including sound, touch, taste, and feel marks) should find protection under the intellectual property laws of Sri Lanka. The original drafters of Sri Lanka's IP legislation omitted this category of marks from the scope of registrable trademarks for extremely valid reasons, such as ...
Keywords: Non-Traditional Trademarks; Sri Lanka